Analisis Perilaku Pengguna Sistem Informasi Akuntansi Oleh Umkm di Masa Pandemi (Studi Kasus Pada UMKM Se-Kota Mataram) - Riani, Ni Putu Dera; Nurabiah (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to determine user behavior towards the acceptance of an accounting information system by micro, small and medium enterprises (MSMEs) during the pandemic in Mataram City, West Lombok. This type of research uses associative research with quantitative methods. This study uses primary data obtained directly by distributing questionnaires to MSMEs in Mataram City. Determination of the sample using the simple random sampling (SRS) technique with the criteria of MSME owners or employees in Mataram City who have used an accounting information system in the process of recording their business transactions, so that a total of 293 respondents were obtained. The data analysis tool used Partial Least Square (PLS). The results of this study indicate that performance expectance, effort expectance, social influence have a significant effect on user interest (behavioral intention). While facilitating conditions and user interest (behavioral intention) have a significant effect on user behavior (use behavior) of the accounting information system.